GABAB receptors suppress burst-firing in reticular thalamic neurons. Issue 6 (2nd November 2017) - Cain, Stuart M.; Garcia, Esperanza; Waheed, Zeina; Jones, Karen L.; Bushell, Trevor J.; Snutch, Terrance P.
ABSTRACT: Burst-firing in thalamic neurons is known to play a key role in mediating thalamocortical (TC) oscillations that are associated with non-REM sleep and some types of epileptic seizure. Within the TC system the primary output of GABAergic neurons in the reticular thalamic nucleus (RTN) is thought to induce the de-inactivation of T-type calcium channels in thalamic relay (TR) neurons, promoting burst-firing drive to the cortex and the propagation of TC network activity. However, RTN neurons also project back onto other neurons within the RTN. The role of this putative negative feedback upon the RTN itself is less well understood, although is hypothesized to induce de-synchronization of RTN neuron firing leading to the suppression of TC oscillations. Here we tested two hypotheses concerning possible mechanisms underlying TC oscillation modulation. Firstly, we assessed the burst-firing behavior of RTN neurons in response to GABAB receptor activation using acute brain slices. The selective GABAB receptor agonist baclofen was found to induce suppression of burst-firing concurrent with effects on membrane input resistance. Secondly, RTN neurons express CaV 3.2 and CaV 3.3 T-type calcium channel isoforms known to contribute toward TC burst-firing and we examined the modulation of these channels by GABAB receptor activation. Utilizing exogenously expressed T-type channels we assessed whether GABAB receptor activation could directly alter T-type calcium channel properties. Overall, GABAB receptor activation had only modest effects on CaV 3.2 and CaV 3.3 isoforms. The only effect that could be predicted to suppress burst-firing was a hyperpolarized shift in the voltage-dependence of inactivation, potentially causing lower channel availability at membrane potentials critical for burst-firing. Conversely, other effects observed such as a hyperpolarized shift in the voltage-dependence of activation of both CaV 3.2 and CaV 3.3 as well as increased time constant of activation of the CaV 3.3 isoform would be expected to enhance burst-firing. Together, we hypothesize that GABAB receptor activation mediates multiple downstream effectors that combined act to suppress burst-firing within the RTN. It appears unlikely that direct GABAB receptor-mediated modulation of T-type calcium channels is the major mechanistic contributor to this suppression.